2004
DOI: 10.1007/s10163-003-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of gold by chicken egg shell membrane-conjugated chitosan beads

Abstract: We have successfully prepared a bead-type adsorbent from two materials with different adsorption characteristics. Heavy metals were removed by greatly swollen egg shell membrane-conjugated chitosan beads. The egg shell membrane accumulated and removed precious metal ions from a dilute aqueous solution with a high affinity in a short contact time. Experiments suggested that chitosan beads could take up gold ions with great capacity and selectivity by conjugation with egg shell membrane. Under certain conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…These experiments suggested that ESM could be promising to use for the purpose of removal and/or recovery of metals and water pollution control. Based on this study, Shoji and colleagues have successfully prepared a bead-type adsorbent from greatly swollen eggshell membrane-conjugated chitosan beads [133]. Competitive adsorption experiments have been performed in mixed solutions containing various metal ions.…”
Section: Samplementioning
confidence: 98%
“…These experiments suggested that ESM could be promising to use for the purpose of removal and/or recovery of metals and water pollution control. Based on this study, Shoji and colleagues have successfully prepared a bead-type adsorbent from greatly swollen eggshell membrane-conjugated chitosan beads [133]. Competitive adsorption experiments have been performed in mixed solutions containing various metal ions.…”
Section: Samplementioning
confidence: 98%
“…22,23 The ESM can also act as a platform to retrieve heavy toxic metal ions, such as arsenic and mercury, from water. 24 Here, we demonstrate the simultaneous in situ reduction of Au and Ag ions by ESM resulting in the formation of highly uorescent AuAg alloy nanoparticles and metal ion immobilized uorescent solid ESM platforms. In addition, we also demonstrate the unique dyeadsorbing capability of these metal ion immobilized ESM platforms for the efficient removal of anionic dyes from waste water at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…Eggshell is seldom used as a source of calcium. Research reports have it that eggshell membrane can be used as a support for bacteria culturing [14], split-thickness graft donor site dressing due to its antiinflammatory properties [15], pain relieving [16], wound protection [17], healing process in mammalian tissues damaged as a result of burns, ulceration, cuts and injuries [18] as well as removal of heavy metals and gold from industrial waste discharge [19].…”
Section: Introductionmentioning
confidence: 99%